Comparative efficacy of Canagliflozin Versus Empagliflozin on oxidative stress – In-Vitro method - DR. M.SINDHUJA; DR N.S MUTHIAH; DR. R. RAJESWARI (International Journal of Pharma and Bio Sciences, 2017)
Diabetes is characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. Hyperglycemia causes auto-oxidation of glucose to form free radical .O2-. The production of free radicals beyond the limit of scavenging activity of endogenous antioxidant defenses result in micro vascular and macro vascular complications. In this study the antioxidant efficacy of Canagliflozin and Empagliflozin was compared by 1, 1-Diphenyl-2-Picrylhydrazyl radical scavenging activity (DPPH) assay and nitric oxide scavenging activity. Sodium-glucose co-transporter-2 inhibitors shows pleotrophic therapeutic potential in the treatment of type II Diabetes. On comparison with ascorbic acid both Canagliflozin and Empagliflozin shows antioxidant property. However empagliflozin has higher efficacy for reducing oxidative stress when compared with canagliflozin.